Exploring Job Satisfaction of Nursing in Fiji - Nawaqaliva, Kesaia Tawa (Auckland University of Technology, 2022)
Globally, nurses are the largest group of health professionals. Their job satisfaction impacts on the delivery of quality health care, patient safety, and a reduction in the burden of disease. Conversely, their job dissatisfaction is associated with attrition, burnout, low morale, staff shortage, adverse patient outcomes, and commonly workforce migration. This study, set in Fiji aimed to explore the factors influencing job satisfaction amongst nurses in order to pose recommendations for improving their work-related conditions. The key research questions were to understand personalised and professionalised meanings of job satisfaction; explore the personal, organisational, managerial, and professional challenges that nurses in Fiji experience; and to recommend strategies that support improvement in work conditions for nurses in Fiji, leading to enhanced job satisfaction. The Fijian Vanua framework provided the theoretical approach that encompassed the Fijian worldview in terms of the way of living, interacting, and sharing knowledge that framed both the epistemology and methodological approach of this study. The three cohorts of participants were recruited included primarily registered nurses working in urban, peri-urban, rural, and remote rural nursing facilities; as well as nursing managers and government officials from the two main divisional areas. Data were collected through individual Talanoa interviews with Fijian nurses(n=20), and two Talanoa focus group discussions with nurse leaders and government administration officials (n=9). Purpose sampling included 5 male and 15 female registered nurses with ages ranging between 27 and 48 years. The two Talanoa focus groups included one for nursing leaders (n = 4) and another for government administration officials (n = 5). They were all females in leadership roles and had between 5- and 10-years’ experience in their respective roles. Both sets of Talanoa focus group participants had background experience in leading or policy making in urban and rural nursing. Thematic analysis was used to identify the embedded themes related to philosophies of the Vanua framework. The four main themes identified were: organisation, management, work, and nurse characteristics; from which eight sub-themes emerged: authoritative decision making, devaluing of nurses, unclear promotion pathways, lack of leadership, workforce environment, stress, burnout and stigma, unsafe working condition, nurses’ roles, and responsibilities. The study recommended that improving the nurses’ working conditions could be facilitated through empowering nursing leaders with management training, improving nursing remuneration, comprehensive review of the nursing scope of practice, nursing inclusion in health policy planning, review of nursing curriculum, and leadership management on mental health. The research found that generalised challenges encountered by the Fiji nurses within the context of their developing country requires comprehensive review of their understanding of job satisfaction shaped strongly by the Vanua and socio-political and cultural contexts.